Att anmäla våld - Malin Åkerström (Nordisk Tidsskrift for Kriminalvidenskab)
Recently violence and victims of violence in Sweden have been the object of massive societal attention and mobilisation. Crime statistics are often used rhetorically in the claims about the seriousness of the problem. The inherent weakness of such data is widely acknowledged among criminologists; they rest on the practice of reporting events to a public agency. The variance in reporting is often explained in terms of either individual rational calculations by individuals (theft: insurance companies require that one report the stolen goods to the Police), or by general norms in society encouraging or inhibiting reporting practices (sexual harassment, rape etc. are often exemplifying a changing moral code reflected in an increased practice of reporting). Here a different theme is explored: the tendency to report as mirroring different local cultures. The societal attention towards violence gave rise to different subcategories; one was violence at work. In a study of violence against hospital staff official studies portrayed mental hospital staff to be most at risk. A survey revealed however that nurses at homes for elderly were as likely to become involved in violent interaction. Qualitative interviews suggested that reporting was encouraged in mental hospitals, while this was not so for staff working with the old. Moreover, staff involved with the elderly hesitated to label physical aggressive events as 'violence' even if they became severely injured.